PENGARUH MEDIA WORDWALL TERHADAP MINAT BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PUISI DI KELAS VIII G SMP NEGERI 7 MUARO JAMBI - Munikmah; Agus Setyonegoro; Arum Gati Ningsih (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
Poetry learning is often considered difficult and less interesting, so their interest in learning this material tends to be low. To overcome this, innovation is needed in the learning process that can increase student interest and involvement. One of the interactive learning media that can be utilized is Wordwall. This study aims to determine the effect of using Wordwall media on students' interest in learning poetry in class VIII of SMP Negeri 7 Muaro Jambi. This study uses a quantitative approach with a quasi-experimental method and one group design. Data collection instruments are in the form of questionnaires and observation sheets that have been tested for validity and reliability. Determination of the sample in this study used purposive sampling and the sample was class VIII G students consisting of 25 students. The results of the study showed that the normality of the data was > 0.05 which means that the data is normally distributed, the homogeneity results showed a Sig value of 0.314 > 0.05 which means that the data has a homogeneous variance. Hypothesis testing was conducted using the t-test, the results of the t-test showed a significance value (Sig. 2-tailed) of 0.000 <0.05 and a calculated t value of 9.259> t table 1.714 so that H0 was rejected and H1 was accepted. Thus, it can be concluded that Wordwall media has an effect on increasing students' interest in learning poetry.